Impact of Physiotherapy on the Calf Muscle Torque Variability after Achilles Tendon Rupture - Vaida Aleknavičiūtė; Rima Solianik; Dovilė Kielė; Laimutis Škikas; Nerijus Masiulis; Albertas Skurvydas (Lithuanian Sports University, 2020)
It has been established that muscle torque variability determines movement stability during the task [1]. Calf muscle weakness, ankle range of motion reduction and postural misbalance are common pathological limitations after Achilles tendon rupture (ATR). Most studies analyse rehabilitation influence for muscle strength and body balance, but there is a lack of information about calf muscle torque variability. The aim of the study was to determine ankle plantar flexion and dorsal flexion muscle maximal voluntary contraction torque and variability Q. Organization and methods. We measured five males, (aged 29 ± 6) after 6.5 - week surgery of ATR. Participants performed isometric ankle flexion and extension force with injured and non-injured legs. Muscles maximal voluntary contraction (MVC) torque and torque variability were measured at -15°; 0°; 15° angles. The variability of target force was 20% of MVC torque. Rehabilitation programme consisted of balance, muscle strength and stretching exercises. Calf muscle MVC torque and variability were observed before and after 8-week rehabilitation. The results of the research. We determined that after physiotherapy the injured and the non-injured leg isometric ankle flexion and extension muscle MVC torque increased and muscle torque variability decreased. Keywords: muscle torque variability, isometric maximal voluntary contraction torque, rehabilitation suformavimas.